Safety Nets and Food Programs in Asia: A Comparative Perspective - Shikha Jha; Ashok Kotwal; Bharat Ramaswami (Asian Development Bank (ADB), 2013)
Many countries adopted safety net programs to deal with the food crisis of 2008. However, such programs are often beset with targeting errors, inefficiencies, and fraud. Despite this, there is no systematic comparative analysis of safety nets. The objective of this paper is to identify generic issues germane to safety net design and their role in determining success. We examine the performance of safety net programs in Bangladesh, India, Indonesia, and the Philippines in terms of people covered, food distributed, and income support provided. These countries spend 1%–3% of their gross domestic product on safety nets - small in relation to developing and industrial economies. We find an across-the-board failure of targeting in the four countries. The reasons range from elite capture, incorrect identification of the poor, their lack of access, barriers to participation, and regional allocation biases. Even if perfect targeting could cover the entire target group and eliminate leakage to nontarget groups, the target groups may not receive the full subsidy due to illegal diversions, operational inefficiencies, and excess costs of public agencies. The success of the safety nets will depend on increasing the participation of the poor and minimizing program waste. Computerization of supply chains to track grain supplies can reduce diversion, and switching from in-kind to cash transfers can cut administrative and other costs of physical handling. The mix of tools would depend upon the economic, political, cultural, and social backgrounds of the country, and its administrative and fiscal capabilities to provide safety net programs.
hdl:11540/2298
Keywords: D60; I38; 330; Conditional and unconditional cash transfers; in-kind transfers; social safety nets; Bangladesh; India; Indonesia; and Philippines